Vegetation Reconstruction From Siberia and the Tibetan Plateau Using Modern Analogue Technique–Comparing Sedimentary (Ancient) DNA and Pollen Data - Liu, Sisi; Li, Kai; Jia, Weihan; Stoof-Leichsenring, Kathleen Rosmarie; Liu, Xingqi; Cao, Xianyong; Herzschuh, Ulrike (Frontiers in Ecology and Evolution, 2021)
To reconstruct past vegetation from pollen or, more recently, lake sedimentary DNA (sedDNA) data is a common goal in palaeoecology. To overcome the bias of a researcher’s subjective assessment and to assign past assemblages to modern vegetation types quantitatively, the modern analogue technique (MAT) is often used for vegetation reconstruction. However, a rigorous comparison of MAT-derived pollen-based and sedDNA-based vegetation reconstruction is lacking. Here, we assess the dissimilarity between modern taxa assemblages from lake surface-sediments and fossil taxa assemblages from four lake sediment cores from the south-eastern Tibetan Plateau and northern Siberia using receiver operating characteristic (ROC) curves, ordination methods, and Procrustes analyses. Modern sedDNA samples from 190 lakes and pollen samples from 136 lakes were collected from a variety of vegetation types. Our results show that more modern analogues are found with sedDNA than pollen when applying similarly derived thresholds. In particular, there are few modern pollen analogues for open vegetation such as alpine or arctic tundra, limiting the ability of treeline shifts to be clearly reconstructed. In contrast, the shifts in the main vegetation communities are well captured by sedDNA. For example, pronounced shifts from late-glacial alpine meadow/steppe to early–mid-Holocene coniferous forests to late Holocene Tibetan shrubland vegetation types are reconstructed for Lake Naleng on the south-eastern Tibetan Plateau. Procrustes and PROTEST analyses reveal that intertaxa relationships inferred from modern sedaDNA datasets align with past relationships generally, while intertaxa relationships derived from modern pollen spectra are mostly significantly different from fossil pollen relationships. Overall, we conclude that a quantitative sedDNA-based vegetation reconstruction using MAT is more reliable than a pollen-based reconstruction, probably because of the more straightforward taphonomy that can relate sedDNA assemblages to the vegetation surrounding the lake.